2009
DOI: 10.1161/strokeaha.109.561670
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Stroke in Heart Failure in the REasons for Geographic And Racial Differences in Stroke (REGARDS) Study

Abstract: Background and Purpose-The prevalence of stroke is increased in individuals with heart failure (HF). The stroke mechanism in HF may be cardiogenic embolism or cerebral hypoperfusion. Stroke risk increases with decreasing ejection fraction and low cardiac output is associated with hypotension and poor survival. We examine the relationship among blood pressure level, history of stroke/transient ischemic attack (TIA), and HF. Methods-We compared the prevalence of self-reported history of stroke or TIA in the REas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Hence, we used current digoxin use as a proxy for heart failure similar to previous REGARDS articles. 21 It has been reported that digoxin use has a specificity of about 99% and a sensitivity of about 28% for the diagnosis of heart failure. 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we used current digoxin use as a proxy for heart failure similar to previous REGARDS articles. 21 It has been reported that digoxin use has a specificity of about 99% and a sensitivity of about 28% for the diagnosis of heart failure. 52 …”
Section: Discussionmentioning
confidence: 99%
“…We used current use of digoxin at baseline as a proxy for heart failure diagnosis similar to previous reports from REGARDS. 21 CHADS2 score (congestive heart failure; hypertension; age, ≥75 years; diabetes mellitus; and prior stroke) was calculated using 1 point for each category except for prior stroke, which was given 2 points. 22 Estimated glomerular filtration rate (eGFR) was calculated using the CKD-EPI equation (Chronic Kidney Disease Epidemiology Collaboration).…”
Section: Methodsmentioning
confidence: 99%
“…We used current use of digoxin at baseline as a proxy for heart failure diagnosis similar to previous reports from REGARDS. 21 CHADS2 score (congestive heart failure; hypertension; age, ≥75 years; diabetes mellitus; and prior stroke) was calculated using 1 point for each category except for prior stroke, which was given 2 points. 22 Estimated glomerular filtration rate (eGFR) was calculated using the CKD-EPI equation (Chronic Kidney Disease Epidemiology Collaboration).…”
Section: Covariatesmentioning
confidence: 99%
“…Hence, we used current digoxin use as a proxy for heart failure similar to previous REGARDS articles. 21 It has been reported that digoxin use has a specificity of about 99% and a sensitivity of about 28% for the diagnosis of heart failure. 52 Data on the actual onset of AF were not available, and therefore we could not adjust for the time between AF onset and baseline visit.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation